Teachers’ Perception of Using Games Based Learning (GBL) In Learning English at Islamic Senior High School In South Sulawesi - Muhammad Idul; Alwi Sibali; Firman; Amaliah Ramdani (Synergy Education Journal of Multidisciplinary Language and Social Sciences, 2026)
This study explores English teachers’ perceptions of using Game-Based Learning (GBL) in English language instruction at Indonesian Islamic senior high schools. Although GBL has been widely recognized for its ability to enhance student engagement and learning outcomes, its implementation in faith-based schools, where religious and cultural considerations play a vital role, remains underexplored. The objective of this study was to examine teachers’ views on the benefits, challenges, and feasibility of integrating GBL in Islamic school settings. A quantitative descriptive approach was employed, and data were collected through a questionnaire distributed to 35 English teachers from several Islamic senior high schools in South Sulawesi. The results revealed that 72% of teachers perceived GBL as effective in increasing student participation, and 65% believed it helped improve vocabulary retention. However, challenges were also identified, including limited access to technology (58%) and concerns about aligning games with Islamic values (45%). Despite these concerns, 68% of respondents expressed willingness to adopt GBL if provided with proper training and culturally appropriate materials. The study concludes that GBL has strong potential to support English instruction in Islamic educational contexts, but successful implementation requires institutional support, teacher development, and the design of faith-aligned educational games.